The Peter pyramid or will we ever get the point ? - Peter, Laurence J. (New York William Morrowand Company Inc., 1986)
Here the wit, wisdom, and uncommon common sense are at their best. A champion of clarity and simplicity, the author skillfully attacks bureaucracy. Though he could probably win the battle on his own, he enlists the help of artful illustrations and apt quotations.
Keywords: Economics